Coordinated Implicitly? An Empirical Study on the Role of Social Media in Collaborative Learning - Zhang, Xi; Chen, Hui; Ordóñez de Pablos, Patricia; Lytras, Miltiadis; Sun, Yongqiang (International Review of Research in Open and Distributed Learning, 2016)
As social media is widely adopted in collaborative learning, which places teams in a virtual environment, it is critical for teams to identify and leverage the knowledge of their members. Yet little is known about how social media influences teams to coordinate their knowledge and collaborate effectively. In this research, we explore the roles of two kinds of social media activity – information processing and social connection in teamwork – by applying communication and transactive memory systems (TMSs) as the mechanisms of explicit and implicit coordination respectively. We test this model using partial least squares (PLS) method by treating team as the unit of analysis. Drawing on the data from a study that involves 40 teams of graduate students performing a complex research report over eight weeks, we find that both TMSs and communication can significantly improve teamwork outcomes, and communication can help teams to better coordinate implicitly. With regard to social media activities, the results reveal that both information processing and social connection can enhance the level of TMSs; however, only social connection is positively related to communication. Unfortunately, information processing cannot significantly strengthen communication quality. The possible reasons are discussed and some theoretical and practical implications are also put forward.